2004
DOI: 10.1038/sj.bjc.6601727
|View full text |Cite
|
Sign up to set email alerts
|

Breast adenocarcinoma liver metastases, in contrast to colorectal cancer liver metastases, display a non-angiogenic growth pattern that preserves the stroma and lacks hypoxia

Abstract: Breast adenocarcinoma liver metastases, in contrast to colorectal cancer liver metastases, display a non-angiogenic growth pattern that preserves the stroma and lacks hypoxia Although angiogenesis is a prerequisite for the growth of most human solid tumours, alternative mechanisms of vascularisation can be adopted. We have previously described a non-angiogenic growth pattern in liver metastases of colorectal adenocarcinomas (CRC) in which tumour cells replace hepatocytes at the tumour -liver interface, preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(180 citation statements)
references
References 28 publications
7
172
1
Order By: Relevance
“…For example, human breast tumours that have metastasized to liver show this phenotype. They have been reported to exhibit little evidence for hypoxia (indicated by expression of the endogenous hypoxia marker protein carbonic anhydrase IX) and express low levels of VEGF 125,126 . Hepatic metastases of colorectal cancer, by contrast, show high levels of carbonic anhydrase IX and increased VEGF and clearly exhibit angiogenesis 125 .…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
“…For example, human breast tumours that have metastasized to liver show this phenotype. They have been reported to exhibit little evidence for hypoxia (indicated by expression of the endogenous hypoxia marker protein carbonic anhydrase IX) and express low levels of VEGF 125,126 . Hepatic metastases of colorectal cancer, by contrast, show high levels of carbonic anhydrase IX and increased VEGF and clearly exhibit angiogenesis 125 .…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%
“…Reports have suggested differences between primary tumours and secondary sites and between different secondary sites. Whereas primary breast tumours grow angiogenesis dependently, we demonstrated that 90% of breast cancer liver metastases grow according to an angiogenesis-independent replacement pattern (Stessels et al, 2004). The growth of breast cancer LN metastases, on the contrary, was angiogenesis dependent and angiogenesis and hypoxia in the metastases were correlated with angiogenesis and hypoxia in the primary tumours .…”
mentioning
confidence: 72%
“…Furthermore, the growth pattern of the skin deposit correlated with the growth pattern of the primary tumour. Breast cancer liver metastases, on the other hand, almost always show a 'replacement' growth pattern (Stessels et al, 2004): breast cancer cells replace hepatocytes at the tumour/liver interface with conservation of the liver plate architecture and cooption of the sinusoidal vasculature of the liver. Almost no hypoxia and no angiogenic switch is seen.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary tumour growth in breast cancer is angiogenesis dependent, we previously showed that 96% of liver metastases of breast cancer grow according to a nonangiogenic replacement pattern, marked by replacement of the hepatocytes by tumour cells without any desmoplastic reaction (Stessels et al, 2004). Thus, breast cancer liver metastases grow by coopting the sinusoidal vessels.…”
mentioning
confidence: 98%